Prognostic prediction of genotype versus phenotype in genetic cardiomyopathies. (3rd October 2022) - Paldino, A; Dal Ferro, M; Stolfo, D; Gandin, I; Graw, S; Gigli, M; Medo, K; Gagno, G; Zaffalon, D; Castrichini, M; Mase', M; Merlo, M; et al.
Abstract: Background: In cardiomyopathies (CMPs), the diverse genetic background often leads to phenotypic heterogeneity. Currently, genotype-phenotype studies are founded on clinical phenotype-based classification of CMPs, contributing possible biases due to the exclusion of specific and unascertained phenotypic expressions of CMP genes. Purpose: We sought to define differences in outcome when stratifying patients based on phenotype at presentation compared with genotype in a large cohort of CMP patients with positive genetic testing. Methods: In this study, we included the whole spectrum of non-hypertrophic CMP phenotypes, genetically determined: dilated cardiomyopathy (DCM), arrhythmogenic right ventricular cardiomyopathy (ARVC), left ventricular arrhythmogenic cardiomyopathy (ALVC) and biventricular ARVC (BiV). The primary and secondary outcomes were: 1) all-cause mortality/heart transplant (D/HT); 2) heart failure-related death/heart transplant/left ventricular assist device implantation (DHF/HT/VAD); and 3) sudden cardiac death/life-threatening ventricular arrhythmias (SCD/MVA). Results: Two hundred and eighty-one patients (80% DCM) carrying pathogenic or likely pathogenic variants were included in this study. The phenotype was classified as DCM, ARVC, ALVC and BiV according to current consensus criteria. The median follow-up was 188 months. Variants in titin (TTN; 34%) and sarcomeric genes (SARC; 22%) were the most frequent genotypes and almost invariably associated with a DCM phenotype. DSP, LMNA and FLNC displayed more heterogeneous phenotypic presentations, including DCM, ARVC, ALVC, BiV. At survival analysis, the arrhythmic outcome occurred more frequently in patients without a DCM phenotype and in carriers of DSP, PKP2, LMNA and FLNC variants. However, after adjustment for age and sex, the genotype-based classification but not the phenotype-based classification was predictive of the arrhythmic outcome. LMNA showed the worst trend in term of D/HT and DHF/HT/LVAD. Conclusions: In genetic cardiomyopathies, genotype is associated with significant phenotypic heterogeneity. Nevertheless, in our study, the genotypic-based classification showed higher precision in predicting CMP patients' outcome in respect to the phenotype-based classification. These findings add to the current understanding of inherited CMPs and may implement the risk stratification of patients with positive genetic testing. Funding Acknowledgement: Type of funding sources: None.